2020
DOI: 10.3390/ma13030530
|View full text |Cite
|
Sign up to set email alerts
|

Surface Analysis of Wire-Electrical-Discharge-Machining-Processed Shape-Memory Alloys

Abstract: Shape-memory alloys such as nitinol are gaining popularity as advanced materials in the aerospace, medical, and automobile sectors. However, nitinol is a difficult-to-cut material because of its versatile specific properties such as the shape-memory effect, superelasticity, high specific strength, high wear and corrosion resistance, and severe strain hardening. Anunconventional machining process like wire-electrical-discharge-machining (WEDM) can be effectively and efficiently used for the machining of such al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
45
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(47 citation statements)
references
References 31 publications
0
45
2
Order By: Relevance
“…It was also observed that a higher value of current causes a frequent wire breakage during cutting. Chaudhari et al [18] worked on surface analysis of shape memory alloy by WEDM. They found that defect-free and better surface finish obtained at optimized values of current, pulse on and off time.…”
Section: Introductionmentioning
confidence: 99%
“…It was also observed that a higher value of current causes a frequent wire breakage during cutting. Chaudhari et al [18] worked on surface analysis of shape memory alloy by WEDM. They found that defect-free and better surface finish obtained at optimized values of current, pulse on and off time.…”
Section: Introductionmentioning
confidence: 99%
“…Shape memory TiNi alloys are materials with unique functional properties, but at the same time have very favorable parameters in terms of mechanical strength, fatigue strength, specific weight, resistance to corrosion and aggressive environments, etc. For this reason, there is a great interest in these materials in the industry of modern instruments or mechanical systems used in technology and medicine [ 11 , 12 , 13 , 14 , 15 ]. However, in order to maintain their high position as construction materials, the costs of their treatment should be reduced.…”
Section: Introductionmentioning
confidence: 99%
“…The second in the hierarchy is the cost of their production. It can be expected that, in the future, due to the need to reduce and optimize production costs, research efforts will be directed toward the processes of shaping NiTi alloy elements using methods that ensure maximum efficiency while maintaining a good quality of the machined surface [ 6 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was determined that most of the contributions mentioned in the literature were found in terms of processing through electrical discharge machining with form copying [ 19 , 20 , 21 ], as well as the study of aspects worthy of consideration regarding issues of objective functions, processing productivity, volume wear, and relative wear [ 22 , 23 , 24 ]. Regarding the transfer object, specific properties of a carbon fiber reinforced polymer with a specific strength and extremely high rigidity, with a relatively low thermal expansion coefficient and a special property, namely the possibility to be able to easily model its surface, can be discussed [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%